National and subnational governance and decision-making processes during the COVID-19 pandemic in Nigeria: an empirical analysis - Mukherjee, Sanjana; Asthana, Sumegha; Ukponu, Winifred; Ihueze, Adachioma C.; Gobir, Ibrahim B.; Phelan, Alexandra L.; Standley, Claire J. (BMJ global health, 2023)
Governance of the COVID-19 pandemic required decision-makers to make and implement decisions amidst uncertainty, public pressure and time constraints. However, few studies have attempted to assess these decision-making processes empirically during health emergencies. Thus, we aimed to understand governance, defined as the process of decision-making and implementation of decisions, during the COVID-19 pandemic in Nigeria. We conducted key informant interviews and focus group discussions with national and subnational government officials, civil society organisation (CSO) members, development partners and academic experts. Our study identified several themes on governance and decision-making processes. First, Nigeria established high-level decision-making structures at the federal and state levels, providing clear and integrated multisectoral decision-making mechanism. However, due to the emergence of conflicts between government levels, there is a need to strengthen intergovernmental arrangements. Second, while decision-makers relied on input from academic experts and CSOs, additional efforts are required to engage such stakeholders in decision-making processes, especially during the early stages of health emergencies. Third, Nigeria’s previous experiences responding to disease outbreaks aided the overall response, as many capacities and coordination mechanisms for cohesive action were present. Fourth, while decision-makers took a holistic view of scientific, social and economic factors for decision-making, this process was also adaptive to account for rapidly evolving information. Lastly, more efforts are needed to ensure decisions are inclusive, equitable and transparent, and improve overall public trust in governance processes. This study provides insights and identifies opportunities to enhance governance and decision-making processes in health emergency responses, aiding future pandemic preparedness efforts.